Students' Perception in Experiencing Reading Descriptive Text Digitally - Subekti, Lodewyk Elfeiand (RETAIN : Journal of Research in English Language Teaching, 2022)
COVID-19 Pandemic makes Indonesian students have to conduct school learning activities from home. It makes the students have to read their books digitally using a mobile phone or laptop which they never did before. This research is intended to know Indonesian students’ perceptions in digital reading and how they adapt to the digital reading in descriptive text. The method used in this research is qualitative research and uses interviews to answer the research question. The students stated they found difficulties in their focus, their eye sore, short battery lifetime problems, uneasiness in finding reading material, and still haven't adapted to digital reading.